Pain related articles published in Thailand in the last 20 years - Sahataya Paiboonworachat (2018)
Background: The Thai Association for the Study of Pain was established 20 years ago with the aim of educating the members and health care providers for pain management and pain research. Objective: Evaluate the progression of pain research by literature survey on Thai journals, since the beginning of TASP. Material and Method: Pain related original articles, except for the abstracts, proceedings, case reports, and review articles, published in eight Thai journals between 1990 and 2009 were searched. Results: The number of pain related articles was 233. The number of articles slowly but gradually increased during 1990 to 2002, drastically increased during 2004 and 2005, and then slightly decreased until 2009. About 75% of the papers were published in Thai language except for those published in one journal that has been published in English. The most common content of articles was related to the acute pain (75%) contributed by anesthesiologists. Conclusion: Pain research has been significantly increasing since the TASP was founded, especially in the last 10 years. The most common area of research is in the field of acute pain. The majority of the articles were published in Thai language.